The role of liver sinusoidal endothelial cells in cancer liver metastasis - Yang, Ming (Am J Cancer Res, 2021)
Liver sinusoidal endothelial cells (LSECs) are the gatekeeper cells in the liver, contributing critical roles in liver physiological and pathological changes. Factors such as dietary macronutrients, toxins, and aging impact LSEC fenestration. Defenestration of LSECs changes their phenotype and function. Under liver injury, capillarized LSECs promote hepatic stellate cells (HSCs) activation and fibrogenesis, while decapillarized LSECs protect the activation of HSCs and liver injury. The expression of chemokines, such as CXCL9 and CXCL16, changes and impacts the infiltration of immune cells in the liver during disease progression, including hepatocellular carcinoma (HCC). As the largest solid organ, liver is one of the most favorable organs into where tumor cells metastasize. The increased interaction and adhesion of circulating tumor cells (CTCs) with LSECs in the local microenvironment and LSEC-induced tolerance of immunity promote cancer liver metastasis. Several strategies can be applied to target LSEC to modulate their function to prevent cancer liver metastasis, including gut microbiota modulation, microRNA therapy, and medical treatment. Delivery of different treatment agents with nanoparticles may promote precise target treatment. Overall, targeting LSECs is a potential strategy for treatment of early liver diseases and prevention of cancer liver metastasis.